2015 Capital investment in the market research and analytics sector: Implosion, correction or normal?. Issue 56 (January 2016) - Chadwick, Simon
Abstract : In 2014, the pace of capital investment into our industry jumped 83% over the prior year. That was on top of an 88% increase in 2013. Nearly $5.8 billion poured into the industry‒seven times higher than in 2011. When will this stop? The answer, it seems, is now .